POLLUTION MONITORING WITH BRACHIONUS CAUDATUS AS BIOINDICATOR - BANDYOPADHYAY, M. K.; SAHA, KEYA; DAS, M. K.; SHARMA, A. P.; MOHANTY, B. P. (Journal of the Inland Fisheries Society of India, 2021)
The animal whose presence in the water body indicates the type and degree of pollution is considered as bioindicator of water pollution. As and when the pollutant gets mixed with any waterbody the residential delicate organisms are eliminated, where as the tolerant species survive and flourish. This imbalance in the aquaticecosystem could be monitored to detect the effect of pollution on the residential organisms. Chandler (1976) gave a biological approach for water quality management and pollution monitoring. A detailed quantification of aquatic biological indicators is known from the work of Philips (1980). Several workers Arora (1965), Gannon and Stemberger (1978), Sladecek (1983) and Takamura et al.(1986) have reported the importance of rotifers and Brachionus spp.in environmental impact assessment study of inland waters. Recently planktons are often used as bioindicator in aquaticecosystem monitoring (Beaugrand et al., 2000; Li et al., 2000).